Still the stranger at the feast?: ideology and the study of twentieth century British politics - Blackburn, Dean (Taylor & Francis, 2017)
This article explores the way in which scholars of twentieth-century British politics have engaged with the concept of ideology. It begins by revisiting Michael Freeden’s seminal intervention on the subject before going on to assess the way in which recent work has challenged, and indeed preserved, older assumptions about the nature and function of political ideas. In doing so, it pursues two objectives: it seeks to demonstrate the consequences of regarding ideas as a significant feature of twentieth-century politics, and it attempts to encourage a more vibrant dialogue between historians and other disciplines that are contributing to the field of ideology studies.